TERT gene harbors multiple variants associated with pancreatic cancer susceptibility. Issue 9 (19th June 2015) - Campa, Daniele; Rizzato, Cosmeri; Stolzenberg‐Solomon, Rachael; Pacetti, Paola; Vodicka, Pavel; Cleary, Sean P.; Capurso, Gabriele; Bueno‐de‐Mesquita, H. B(as); Werner, Jens; Gazouli, Maria; Butterbach, Katja; Ivanauskas, Audrius; et al.
<x xml:space="preserve">Abstract</x> A small number of common susceptibility loci have been identified for pancreatic cancer, one of which is marked by rs401681 in the TERT–CLPTM1L gene region on chromosome 5p15.33. Because this region is characterized by low linkage disequilibrium, we sought to identify whether additional single nucleotide polymorphisms (SNPs) could be related to pancreatic cancer risk, independently of rs401681. We performed an in‐depth analysis of genetic variability of the telomerase reverse transcriptase (TERT) and the telomerase RNA component (TERC) genes, in 5, 550 subjects with pancreatic cancer and 7, 585 controls from the PANcreatic Disease ReseArch (PANDoRA) and the PanScan consortia. We identified a significant association between a variant in TERT and pancreatic cancer risk (rs2853677, odds ratio = 0.85; 95% confidence interval = 0.80–0.90, p = 8.3 × 10−8). Additional analysis adjusting rs2853677 for rs401681 indicated that the two SNPs are independently associated with pancreatic cancer risk, as suggested by the low linkage disequilibrium between them (r2 = 0.07, D′ = 0.28). Three additional SNPs in TERT reached statistical significance after correction for multiple testing: rs2736100 (p = 3.0 × 10−5), rs4583925 (p = 4.0 × 10−5) and rs2735948 (p = 5.0 × 10−5). In conclusion, we confirmed that the TERT locus is associated with pancreatic cancer risk, possibly through several independent variants.